Plasma Glutathione Concentrations in Non-infected Infants Born From HIV-infected Mothers: Developmental Profile - Chantry, Caroline J.; Rodríguez, Jorge L.; Febo, Irma; Díaz, Clemente; Rodríguez-Orengo, José F. (Puerto Rico Health Sciences Journal, 2014)
see manuscript